Newspapers, politics and society: Republican Publications in Castellón during the Democratic Sexenio (1868-1873) - Pallardó Pardo, Esther (Historia y Comunicación Social, 2014)
This work was created with the aim of carrying out an approach to the origin of the party press in the province of Castellón, after the curiosity aroused by a historical period characterized by important political conquests. This research stems from the need to better understand the historical period in which the foundations of a nascent democratic system, which has been consolidated over the years. And to know how that reality was transmitted by the newspapers.
Keywords: Press; Politics; Society; Democratic Sexenio; Castellón.